Co-delivery of paclitaxel and cisplatin with biocompatible PLGA–PEG nanoparticles enhances chemoradiotherapy in non-small cell lung cancer models. Issue 30 (20th July 2017) - Tian, Jing; Min, Yuanzeng; Rodgers, Zachary; Au, Kin Man; Hagan, C. Tilden; Zhang, Maofan; Roche, Kyle; Yang, Feifei; Wagner, Kyle; Wang, Andrew Z.
Abstract : Nanoparticles co-loaded with paclitaxel and cisplatin potently enhance chemoradiotherapy in non-small cell lung cancer models versus the conventional free drug combination by delivering a precise therapeutic ratio. Abstract : Chemoradiotherapy (CRT) with paclitaxel (PTX) and cisplatin (CP) is part of the standard of care for patients with locally advanced non-small cell lung cancer (NSCLC). Despite its high treatment intensity, many patients still develop local recurrence after treatment. Thus, there is a strong need to further improve CRT for lung cancer. One strategy is to co-deliver cytotoxic chemotherapy agents using biocompatible nanoparticles (NPs) which can limit off-target tissue toxicity and improve therapeutic efficacy. Herein, we report the development of dual-drug loaded nanoformulations that improve the efficacy of CRT for NSCLC by co-encapsulation of cisplatin (CP) and PTX in PLGA–PEG NPs. Mice bearing NSCLC xenografts were administered with dual-drug loaded NPs during CRT, which showed greater inhibition of tumor growth than free drug combinations or combinations of single-drug loaded NPs. These results indicate that using a NP co-delivery strategy for this common CRT regimen may improve clinical responses in NSCLC patients.